Genetic characterisation of oyster populations along the north-eastern coast of Tunisia - Dridi, S.; Romdhane, M. S.; Heurtebise, Serge; El Cafsi, M.; Boudry, Pierre; Lapegue, Sylvie (African Journal of Marine Science, 2008)
The taxonomy of oysters has been traditionally based on characteristics of the shell. More recently, the analysis of protein and DNA polymorphism has provided a means to overcome difficulties in distinguishing the different species of oysters based solely on shell morphology. In order to identify oysters of the Tunisian north-east coast, we sequenced a 16S rRNA mitochondrial fragment from 68 oysters sampled from the Bizert Lagoon and the Gulf of Hammamet in northern Tunisia. Comparison of oyster 16S rRNA sequences available in GenBank showed the presence of both Ostreola stentina and Crassostrea gigas in our samples, which could not be detected on the basis of shell morphology only. These data confirmed that C. gigas, a non-native species, is now naturalised in the Bizert Lagoon. Furthermore, significant levels of genetic divergence among the 16S rRNA haplotypes from O. stentina populations have been observed. Specifically, the haplotypes found in the Bizert Lagoon are closer to those previously detected from Morocco and Portugal, whereas those in the Gulf of Hammamet are closer to the haplotypes from the south of Tunisia, with a divergence ranging from 2.1% to 2.7% between the northern and eastern Tunisian haplotypes. The possible impact of the Siculo-Tunisian Strait on the phylogeography of O. stentina is discussed.